KEPEMILIKAN HAK ATAS TANAH ULAYAT PADA MASYARAKAT ADAT DI NAGARI PANGKALAN KECAMATAN PANGKALAN KOTO BARU - Berma, Avnesyia Tri; Hendra, Rahmad; ', Firdaus (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
Every community is in need of soil in his life, in the indigenous communities have a name which is the customary rights of indigenous peoples rights group over a piece of land called communal land. Implementation of communal rights should be based kapentingan national and state that does not conflict with other regulations, can be seen in Article 3 of Law No. 5 of 1960 on the Basic Regulation of Agrarian, but it can also be seen in Article 2 paragraph (2) Regional Regulation West Sumatra province that benefits for the benefit of indigenous peoples and in the rules of customary law Minangkabau any decision should be based on consultation and consensus. However, the case for customary land were sold and its use no longer compatible with the existing rules. The purpose of this thesis, namely: first, to know the background of customary land rights disputes in villages Base, both to know the management of communal land by indigenous people in the village base, third mediation customary land rights in villages Base.This type of research can be classified in this type of sociological research, because in this study the authors directly conduct research on location or area under study in order to provide a complete and clear picture of the problem under study. This research was conducted in villages Base districts Base Koto Baru, while the sample population is a whole party with regard to the issues examined in this study, the data source used primary data and secondary data, data collection techniques in this study with interviews and literature study.From the research, there are three main things that can be inferred. First, the background or the causes of communal land dispute is due to the daily needs of the different indigenous peoples so as to meet the needs of the community will carry out the various ways that lead to the emergence of disputes. Second, their land use is not in accordance with the interests of indigenous peoples have even cause harm to indigenous people themselves. Third, indigenous peoples are less trusting density Adat (KAN) in resolving disputes resulted in communal land settlement to the District Court. Suggestions writer, first, indigenous peoples must mengedapankan common interest and does not conflict with personal interests so that there are no losers. Secondly, the use of communal land should be guided by the existing rules so that there is no abuse of power. Third, KAN should perform its functions optimally, so that indigenous people will trust KAN in resolving land disputes which occurred in the village communal Base.Keywords: Land Rights - Communal Land - Dispute